ANALISIS MODAL SOSIAL TERHADAP KEBERLANJUTAN KEHIDUPAN SOSIAL EKONOMI NELAYAN DI PONDOK BESI, KOTA BENGKULU - Safas, Putri Nikmah; Heriyanti, Lesti; Wijayanti, Ayu (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The social and economic life of fishermen in Pondok Besi, Bengkulu City, is full of diverse and complex problems. Fishermen are often trapped in a cycle of poverty due to changes in income, climate change, and limited access to technology and information. The poverty rate in Indonesia in September 2022 was 9.57%, with Bengkulu as the seventh poorest province in all of Indonesia and second in Sumatra, according to Statistics Indonesia (2023). This suggests that fishing communities, which rely heavily on marine resources, face economic problems. The focus of this research is the way social capital can improve the economic sustainability of fishermen. Data was collected through observation, documentation, and in-depth interviews using a descriptive qualitative approach. Results show that fishermen in Pondok Besi earn between IDR 150,000 and IDR 700,000 per day, with an average income of IDR 1,000,000 per month. Their income is highly influenced by seasonal changes. Strong social capital is demonstrated by trust, social norms and extensive social networks. They play an important role in supporting fishers' economic activities and overcoming economic challenges. Improving the welfare and economic sustainability of fishers in this area is crucial.